2015
DOI: 10.1002/advs.201500136
|View full text |Cite
|
Sign up to set email alerts
|

Local Versus Long‐Range Diffusion Effects of Photoexcited States on Radiative Recombination in Organic–Inorganic Lead Halide Perovskites

Abstract: Radiative recombination in thin films of the archetypical, high‐performing perovskites CH3NH3PbBr3 and CH3NH3PbI3 shows localized regions of increased emission with dimensions ≈500 nm. Maps of the spectral emission line shape show narrower emission lines in high emission regions, which can be attributed to increased order. Excited states do not diffuse out of high emission regions before they decay, but are decoupled from nearby regions, either by slow diffusion rates or energetic barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 34 publications
2
36
1
Order By: Relevance
“…[30,31] It has also been noted in confocal microscopy imaging measurements where the excitation laser is focused in a diffraction limited spot (typically < 1 mm), the observed PL kinetics contains contribution of carrier diffusion out of the excitation/PL collection spot, which can influence the reliable determination of the spatial variation of intrinsic carrier lifetime. [23,32] Nevertheless, it is now widely believed that the morphological heterogeneity incurs deleterious local optoelectronic properties in perovskite films, [25][26][27][28][29]33] although the mechanism by which the morphology influence performance remains unclear. Thus, the ability to probe the effect of morphological heterogeneity on carrier lifetime and mobility and the consequent device performance is essential for the rational improvement of solar cell performance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[30,31] It has also been noted in confocal microscopy imaging measurements where the excitation laser is focused in a diffraction limited spot (typically < 1 mm), the observed PL kinetics contains contribution of carrier diffusion out of the excitation/PL collection spot, which can influence the reliable determination of the spatial variation of intrinsic carrier lifetime. [23,32] Nevertheless, it is now widely believed that the morphological heterogeneity incurs deleterious local optoelectronic properties in perovskite films, [25][26][27][28][29]33] although the mechanism by which the morphology influence performance remains unclear. Thus, the ability to probe the effect of morphological heterogeneity on carrier lifetime and mobility and the consequent device performance is essential for the rational improvement of solar cell performance.…”
mentioning
confidence: 99%
“…[24] Recent imaging studies have reported that PL or cathodoluminescence intensity and decay kinetics varied greatly (< 10 ns to 100 s ns) from grain to grain and from grain interior to boundaries even in large-grained and high performing perovskite thin films. [25][26][27][28][29] These spatial variations of PL decays are attributed to a heterogeneous distribution of defects, which induce fast non-radiative carrier recombination, [25,28,29] and grain boundaries are believed to be the major regions with higher defect densities. [25] In contrary, some other theoretical and experimental studies also suggested that grain boundaries have negligible or even beneficial impact on the performance of perovskite solar cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The materials do not appear amorphous. From these results it is possible to hypothesize a correlation between the local variation in photoluminescence [1,5] and phase and orientation of the perovskite domains, within both the bromide and the iodide based perovskites. STEM EDX analysis was performed in order to study the local chemical composition and to assess the relative differences in the elemental composition.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, for the characterization of PSCs, PL-based methods are widely used. While local time and spectrally resolved PL measurements are more widely reported [35]- [39], there is also an increasing number of spatially resolved studies [40]- [44].…”
mentioning
confidence: 99%